2014
DOI: 10.1161/jaha.114.001250
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Early Aspirin Use Among Patients With Acute Myocardial Infarction in China, 2001–2011: The China PEACE‐Retrospective AMI Study

Abstract: BackgroundAspirin is an effective, safe, and inexpensive early treatment of acute myocardial infarction (AMI) with few barriers to administration, even in countries with limited healthcare resources. However, the rates and recent trends of aspirin use for the early treatment of AMI in China are unknown.Methods and ResultsUsing data from the China Patient‐centered Evaluative Assessment of Cardiac Events Retrospective Study of Acute Myocardial Infarction (China PEACE‐Retrospective AMI Study), we identified a coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 15 publications
3
11
0
Order By: Relevance
“…In the frame of secondary prevention, this study pointed out a large underprescription of antiplatelets in older people. This finding is consistent with other studies and may reflect concerns about the risk of bleeding. However, even if older people may be at high risk of adverse drug events, their risk for the adverse consequences of no treatment are likely to be substantially higher .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the frame of secondary prevention, this study pointed out a large underprescription of antiplatelets in older people. This finding is consistent with other studies and may reflect concerns about the risk of bleeding. However, even if older people may be at high risk of adverse drug events, their risk for the adverse consequences of no treatment are likely to be substantially higher .…”
Section: Discussionsupporting
confidence: 93%
“…In the frame of secondary prevention, this study pointed out a large underprescription of antiplatelets in older people. This finding is consistent with other studies [37][38][39] and may reflect concerns about the risk of bleeding. However, even if older people may be at high risk of adverse drug events, their Table 3 Profiles of appropriateness of antiplatelet drug prescription in prescribed and non-prescribed patients according to primary and secondary prevention of cardiovascular disease risk for the adverse consequences of no treatment are likely to be substantially higher [2].…”
Section: Figuresupporting
confidence: 93%
“…6 In parallel with insurance reform, evidence-based guidelines for secondary prevention of IHD and stroke were published 7–9. Hospital-based studies suggest these developments have been accompanied by improvements in the treatment for secondary CVD prevention 10. However, community physicians lack awareness of the secondary prevention recommendations 11.…”
Section: Introductionmentioning
confidence: 99%
“…The activated complex goes on to phosphorylate IκB-α, causing its ubiquitin-mediated degradation and release of the NF-κB subunits ( Yang et al, 2017 ). And lots of evidence has shown that aspirin’s inhibitory effect of NF-κB has a close relationship with downregulation of IKK-β activity ( Gao et al, 2014 ). Then, we detected whether GC has the similar impact like aspirin on IKK-β activity.…”
Section: Discussionmentioning
confidence: 99%